PENGARUH PENGGANTIAN POLLARD DENGAN DEDAK PADI YANG DISUPLEMENTASI MULTIVITAMIN-MINERAL DALAM RANSUM TERHADAP PERFORMA PRODUKSI BABI RAS PERSILANGAN - Stradivari G. E.; I. B. G. Partama; I G. N. G. Bidura (Fakultas Peternakan Universitas Udayana, 2019)
The purpose of this study is to determine the effect of pollard replacement with rice bran supplementedmultivitamin-mineral in ration on the performance of crossbred pigs. The design used a randomized block design(RBD) consists of 3 treatments and 4 groups as replications. The treatments A (control): pollard in ration withoutmultivitamin-mineral supplementation, B: ration with rice bran without multivitamin-mineral supplementation,C: ration with rice bran which supplemented with 0.20% multivitamin-mineral. The variables observed were finalbody weight, weight gain, feed consumption, FCR, protein, crude fiber, and fat consumption.The results showedthat the ration with rice bran supplemented with 0,20% multivitamin-mineral were able to produce the same finalweight, weight gain, and FCR with the control and increase significantly crude fiber consumption 45,57 g/h, 85,63g/h of fat consumption, and decrease 207,64 g/h protein consumption. However, the feed consumption showed nosignificant differences in each treatment. It can be concluded that pollard replacement with rice bran supplementedwith 0,20% multivitamin-mineral in ration fed to crossbred pigs can produce similar production performance ascontrol, and increase consumption of crude fiber, and fat consumption.